Quality of Life among Postmenopausal Women: A Community-based Cross-sectional Study - Parajuli, Surya Bahadur; KC, Heera; Mishra, Seema Kumari; Luitel, Anish (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: Postmenopausal women have various problems that may affect their quality of life. However, published reports from nearby communities of the capital of province 1 of Nepal are lacking. Hence, we aimed to determine the quality of life of postmenopausal women in selected communities of Morang, Nepal. Methods: This cross-sectional study was conducted from August to October 2021 among 200 postmenopausal women of Budhiganga Rural Municipality. Menopause-specific quality of life (MENQoL) that included vasomotor, psychological, physical, and sexual domains was assessed. Factors that may affect it were also assessed. Results: Majority of the participants had sweating (80.5%), accomplishing less than earlier (95.0%), decrease in physical strength, feeling lack of energy (98.1%), and avoiding intimacy (98.5%) in vasomotor, psychosocial, physical, and sexual domains respectively. The highest mean score was found in the sexual (5.02 ± 0.82) followed by physical (3.43 ± 0.51), vasomotor (3.0 ± 1.08), and psychosocial domain (2.74 ± 0.80). The MENQoL score was 3.48 ± 0.53 with a significant association with age and occupation. The psychosocial domain had a significant association with age, marital status, occupation, history of childbirth, current smoking, and current alcohol use. The physical domain had a significant association with age, religion, marital status, occupation, and history of childbirth. The sexual domain had a significant association with age and current alcohol use. Conclusion: Sexual domain was the most affected in postmenopausal women followed by physical, vasomotor, and psychosocial domain. Age, occupation, marital status, history of childbirth, current smoking, and current alcohol use were the factors associated with MENQoL.